An exploratory study of cognitive complexity at a military intermediate service school - Laurence, Harold A. IV (Kansas State University, 2015)
The military devotes significant resources and time in the development of officers through education. Recently, there has been a great deal of emphasis placed on military Intermediate Service Schools (ISS’s) to enhance the ability of graduates to think with greater cognitive complexity in order to solve the kinds of problems they may face after graduation. The military environment in which these mid-career officer students will serve is highly complex and requires a significant ability to generate solutions to unique and complex problems. One hallmark of a developmental adult educational experience is the advancement of the student to higher levels of cognitive complexity. The purpose of this research was to determine if there was a relationship between the cognitive complexity of faculty, students, and expectations for student graduates, at a military Intermediate Service School. Along with the simultaneous measure of cognitive complexity, via a survey administration of the LEP instrument, the researcher also developed a technique for translating learning objectives from Blooms taxonomy into a corresponding Perry position. This translation method was used to translate the college learning objectives into an expected Perry position for graduates of the college. The study also included demographic data to look for significant results regarding a number of independent variables. For faculty only these included teaching department, years of teaching experience, age, and military status. For both populations the variables studied included education level, gender, combat experience and combat trauma, branch of service, commissioning source, and years of active duty service. The study found that the mean cognitive complexity of entering students (CCI = 360) was lower than the cognitive complexity required of graduates (CCI = 407). However, the faculty mean cognitive complexity (CCI = 398) was not significantly different from a student graduate. The faculty results indicated that there were no statistically significant relations between the independent variables studied and the measured cognitive complexity. For students there was a statistically significant relation between measured cognitive complexity and gender.
Keywords: Cognitive complexity; Military; Learning Environment Preferences; Perry position; Developmental teaching; Bridging; Adult Education (0516)